Homology modeling of human DNA repair protein RAD51 homolog 3 (RAD51C) in breast cancer / Ruzianisra Mohamed ... [et al.] - Mohamed, Ruzianisra (Faculty of Pharmacy, 2024)
Breast cancer is known as one of the most predominant cancers that affect both females and males worldwide. The most crucial risk factor in breast cancer is the mutations in the RAD51C gene that have been considered in most hereditary breast cancers. RAD51C, the RAD51 paralogs, is also a deoxyribonucleic acid (DNA) repair protein related to breast and ovarian cancers. DNA double-strand breaks (DSBs) account for the significant detrimental form of DNA damage. RAD51C mutants also have been recognized in breast/ovarian cancer patients. However, the role of the RAD51C protein in hereditary breast cancer and its three-dimensional (3D) structures remains unclear. Thus, this study was conducted to identify the 3D structure of RAD51C protein from its amino acid sequences. The homology modeling for the 3D structure of the RAD51C protein was carried out by using three automated webservers: I-TASSER, SWISS-MODEL, and Phyre2. PyMOL was applied to visualize the 3D structure of RAD51C protein. Next, the MolProbity, ProSA, and SAVES v6.0 programs have been employed to check the stereo-chemical quality of RAD51C protein. The RAD51C-IT models were found to be the best models for the RAD1C protein after being evaluated and validated, and the models were constructed using full-length RAD51C protein sequences. Thus, these protein models can be utilized as a virtual screening tool in discovering potential inhibitors of RAD51C protein.